Development of Molecularly Imprinted Polymer Materials as Selective Recognition Elements for Electrochemical Meropenem Sensors - Herlina Herlina; Ahmad Hafizullah Ritonga; Andy Febriady; Asvia Rahayu; Naomi Geraldin Sinaga (Jurnal FARMASIMED (JFM), 2025)
The rising prevalence of bacterial resistance to carbapenem antibiotics, particularly meropenem, highlights the urgent need for rapid, selective, and efficient detection methods. This study reports the synthesis of molecularly imprinted polymers (MIPs) based on methyl methacrylate (MMA) as selective recognition elements for electrochemical meropenem sensors. Bulk polymerization was employed using MMA as the functional monomer, ethylene glycol dimethacrylate (EGDMA) as the crosslinker, dimethyl sulfoxide (DMSO) as the porogen, and benzoyl peroxide (BPO) as the initiator. Both non-imprinted polymers (NIPs) and molecularly imprinted polymers (MIPs) were prepared, followed by template extraction through sequential washing with acetonitrile, methanol–acetic acid, and methanol–deionized water to generate specific recognition cavities. Characterization using Fourier Transform Infrared Spectroscopy (FTIR) and Scanning Electron Microscopy (SEM) confirmed the success of molecular imprinting, as evidenced by the disappearance of characteristic meropenem bands and the formation of porous cavities in the MIP. Adsorption studies revealed that the MIP exhibited a higher adsorption capacity (8.9940 mg/g) compared to the NIP (3.9904 mg/g), yielding an imprinting factor (IF) of 2.25. Selectivity testing against the competing analyte amoxicillin produced a selectivity coefficient (α) of 1.06, indicating preferential binding toward meropenem despite modest discrimination. These results demonstrate that MMA–EGDMA-based MIPs possess promising potential as selective recognition elements for electrochemical meropenem sensors. The developed material not only contributes to the advancement of functional polymer research but also offers practical opportunities for real-time monitoring of antibiotic levels in clinical and environmental samples.